Relation of epidermal growth factor receptor expression to goblet cell hyperplasia in nasal polyps - Burgel, Pierre-Regis; Escudier, Estelle; Coste, Andre; Dao-Pick, Trang; Ueki, Iris F.; Takeyama, Kiyoshi; Shim, Jae Jeong; Murr, Andrew H.; Nadel, Jay A. (Journal of allergy and clinical immunology, 2000)
Background: Because the epidermal growth factor receptor (EGFR) system regulates mucin production in airway epithelium, we hypothesized a role for this system in mucus hypersecretion that occurs in nasal polyposis. Objective: We examined the relationship between goblet cell hyperplasia, EGFR expression, and inflammatory mediators produced by eosinophils and neutrophils in nasal polyp tissues. Methods: Nasal polyp tissue samples from 8 patients and nasal turbinate biopsy specimens from 6 normal control subjects were examined for alcian blue/PAS staining, mucin MUC5AC (MUC5AC), and EGFR immunoreactivity and EGFR gene expression (in situ hybridization). We also examined the role of eosinophils and neutrophils in goblet cell hyperplasia. Results: In control nasal mucosa alcian blue/periodic acid–Schiff– and MUC5AC-stained areas were 18.40% ± 1.31% and 21.89% ± 1.43%, respectively. In polyps the alcian blue/periodic acid–Schiff– and MUC5AC-stained areas were 51.30% ± 5.85% and 52.07% ± 6.58%, which was significantly larger than that found in control subjects (each comparison, P < .01). Four of 6 control specimens expressed EGFR messenger RNA and protein weakly in the epithelium. In polyps 4 of 8 specimens expressed EGFR gene and EGFR protein strongly; the EGFR-stained area was greater in hyperplastic than in pseudostratified epithelium. TNF-α immunoreactivity, expressed in eosinophils, was increased in EGFR-positive polyps compared with EGFR-negative polyps, suggesting a role for TNF-α in EGFR expression. Neutrophils were increased in the epithelium of EGFR-positive compared with EGFR-negative polyps, suggesting a role for these cells in mucin expression and in goblet cell degranulation. Conclusion: These data suggest a role for EGFR cascade in the regulation of goblet cell mucins in nasal polyps. Proof of concept will require clinical studies using selective EGFR inhibitors. (J Allergy Clin Immunol 2000;106:705-12.)